ANALYSIS AND SYNTHESIS OF ENHANCED BEE COLONY OPTIMIZATION WITH THE TRADITIONAL BEE COLONY OPTIMIZATION TO SOLVE TRAVELLING SALES PERSON PROBLEM - Agrawal, Prateek; Kaur, Harjeet; Bhardwaj, Deepa (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
Bee colony optimization is the recent swarm intelligence technique which has been applied to solve many combinatorial problems. In this paper we propose the enhanced bee algorithm based on Kmeans clustering to solve TSP. In the proposed algorithm parallel bee algorithm has been applied to each cluster and connection method has been suggested to combine the sub tour to global tour of the whole cities. It was found the enhanced bee algorithm give the better result and more optimal tour.